Management of obstructive sleep apnoea in a primary care vs sleep unit setting: a randomised controlled trial. Issue 12 (31st July 2018) - Tarraubella, Nuria; Sánchez-de-la-Torre, Manuel; Nadal, Nuria; De Batlle, Jordi; Benítez, Iván; Cortijo, Anunciación; Urgelés, Maria Cruz; Sanchez, Virginia; Lorente, Iñigo; Lavega, M Mercé; Fuentes, Araceli; Clotet, Joan; et al.
Abstract : Objective: To assess the effectiveness and cost-effectiveness of primary care (PC) and sleep unit (SU) models for the management of subjects with suspected obstructive sleep apnoea (OSA). Methods: Multicentre, open-label, two-arm, parallel-group, non-inferiority randomised controlled trial. A total of 302 subjects with suspected OSA and/or resistant hypertension were consecutively enrolled, 149 were treated at 11 PC units and 153 patients at a SU. The primary outcomes were a 6-month change in the Epworth Sleepiness Scale (ESS) score and Health Utilities Index (HUI). The non-inferiority margin for the ESS score was −2.0. Results: A total of 80.2% and 70.6% of the PC and SU patients were diagnosed with OSA, respectively, and 59.3% and 60.4% of those were treated with CPAP in PC and SU units, respectively. The Apnoea–Hypopnoea Index was similar between the groups (PC vs SU (median (IQR); 23.1 (26.8) events/h vs 21.8 (35.2) events/h), and the baseline ESS score was higher in the PC than in the SU group (10.3 (6.6) vs 9 (7.2)). After 6 months, the ESS score of the PC group decreased from a mean of 10.1 to 7.6 (−2.49; 95% CI −3.3 to −1.69), and that of the SU group decreased from 8.85 to 5.73 (−3.11; 95% CI −3.94 to 2.28). The adjusted difference between groups for the mean change in the ESS score was −1.25 (one-sided 95% CI −1.88; p=0.025), supporting the non-inferiority of PC management. We did not observe differences in the HUI between groups. The cost analysis showed a median savings of €558.14/patient for the PC setting compared with the SU setting. Conclusions: Among patients with suspected OSA, the PC model did not result in a worse ESS score or HUI than the specialist model and generated savings in terms of management cost. Therefore, the PC model was more cost-efficient than the SU model. Trial registration: Results; >>NCT02234765, Clinical Trials.gov.